Factors Affecting the Best Practices in Performance Management of Royal Irrigation Department - บรรพต, ณิชกานต์; สอนศรี, กมลพร (Journal of Politics and Governance, 2018)
This research aims to study the best practice level of the performance management of the Royal Irrigation Department, study the factors affecting the best practice of the performance management of the Royal Irrigation Department, and distill the lessons of the performance management of the Royal Irrigation Department. The mixed methods were used for this research. The sample groups consisted of 376 central staffs of the Royal Irrigation Department. Four key informants who supervised the performance management process of the Royal Irrigation Department were Director of Human Resources Management Bureau, Expert on Human Resources Management, Director of Human Resources Development Section, and Director of Technical Affairs and Personnel Evaluation Section, Royal Irrigation Department. The research tools consisted of the questionnaires and the interview forms. The research results found that the opinions about the best practice of the performance management of the Royal Irrigation Department were at a high level. After considering each aspect, the researcher found that every step was at a high level. The external factors on the government policy and technology and the internal factors on organizational support, organizational communication, and transformational leaders affected the best practice of the performance management, respectively. Every individual factor did not affect the best practice of the performance management. As for the developmental guidelines of the performance management, the Royal Irrigation Department should continuously use the information technology to manage the performance. There should be the organizational support and administrators. There should be clear performance management process. The main indicators should be standardized and challenging. The organization should enable staffs to be aware of the importance of the performance management. The lessons of the performance management of the Royal Irrigation Department could be distilled as follows: The performance management should be suitably developed. The technology system for the performance management should be developed. The indicators should be standardized.